Toxicity of Per- and polyfluoroalkyl substances in elutriates prepared with estuarine and freshwater sediments - Paige M. Krupa; Guilherme R. Lotufo; Jonna Boyda; Nicolas L. Melby; Ashley N. Kimble (Ecotoxicology and Environmental Safety)
PFAS has a ubiquitous environmental occurrence, posing challenges to sediment management. To address data gaps concerning release of PFAS from sediment to the water column during dredged material aquatic placement or other sediment resuspension activity, we generated elutriates from PFAS-contaminated sediments. Sediments were obtained from both freshwater and estuarine environments, with a field-collected sediment representative of contaminated areas and a spiked sediment with concentrations exceeding levels frequently measured at contaminated sites. We then conducted acute toxicity tests of the elutriates with species standardly used in dredging evaluations: the sheepshead minnow (Cyprinodon variegatus), the fathead minnow (Pimephales promelas), the water flea (Ceriodaphnia dubia), and the Mysid shrimp (Americamysis bahia). PFAS partitioning to sediment and organic matter was observed to increase with carbon chain length. PFAS-induced mortality was not observed in any of the four test species, as measured concentrations of PFAS were below levels known to cause negative effects in these organisms. Though PFAS concentrations in the spiked sediment elutriates exceeded concentrations known to cause effects in the most sensitive aquatic species, PFAS levels in the more environmentally relevant field-collected sediment elutriates did not. Consequently, PFAS released from the sediment to the water column is not expected to cause toxicity to pelagic biota during aquatic placement of dredged material.